An Advanced IoT Based Frame Work to Save Electrical power in an Organization - Zubair, Swaleha; Aalam, Uzair (International Journal of Computer Sciences and Engineering, 2019)
The growing global demand for power supply is likely to exhaust available resources soon. It is advisable to avoid wastage of electricity as it may overburden consumer adversely. In the present study, we propose an IoT based solution to reduce electric power wastage in organizations. As the organizations are generally divided into sub sections or departments, a frame work can be proposed which allows the managers and supervisors to keep an online track of the ON/OFF status of appliances in their respective departments/sectors. The access to appliances can be provided with a Secure Shell connection through a dedicated server which keeps monitoring all the appliances in the whole organization continuously. Each manager and in-charge along with other officials can be provided with a user ID and password to login with. Each of them is likely to entertain with different level of rights to control various gadgets of the department. This frame work can prove itself to be useful in reducing the problem of various appliances ON in an organization. The frame work has provision for further improvements such that with slight modification it can be implemented controlling and monitoring a weather station situated in the remote forest.